BUDAYA DAN WILLINGNESS TO ACCEPT (WTA) KOMPENSASI ATAS ALIH FUNGSI LAHAN PERTANIAN DI KABUPATEN GIANYAR: KASUS BANJAR BANGKIANSIDEM, DESA KLIKI, TEGALALANG - Yudha, I Made Endra Kartika; Utama, Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.08.TAHUN 2020, 2020)
Environmental damage and the conversion of agricultural land have become problems that will affect human life. Industrial development and the construction of tourist accommodation such as hotels and restaurants have caused various impacts. The environmental impact of tourism activities also occurs in Gianyar Regency, the indicator is the conversion of agricultural land functions. For this reason, it is necessary to know the value of willingness to accept (WTA) to compensate for the conversion of agricultural land in Gianyar Regency by taking and cultural factors that explain the value of this WTA. The average value of WTA for compensation for the conversion of community land in Kliki Village is Rp.217,500.- per month. A cultural factor is formed that is used to explain the value of WTA. These cultural factors are formed by 4 variables and have one variable with the highest loading factor which is the average time of customary activities.